2021
DOI: 10.3390/su132312983
|View full text |Cite
|
Sign up to set email alerts
|

Building Information Modeling (BIM) for Construction and Demolition Waste Management in Australia: A Research Agenda

Abstract: Construction and demolition waste (C&DW) contribute to approximately 30% of the total waste generation worldwide, by which heterogeneous ecological impacts, such as resource depletion, global warming, and land degradation, are engendered. Despite ongoing research efforts to minimize construction waste via the Building Information Modeling (BIM)-aided design, there is a paucity of research on integrating BIM in demolition waste management (DWM). This study investigates prominent barriers and future research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 94 publications
(146 reference statements)
0
25
0
2
Order By: Relevance
“…Research and Development (R&D) [15], [30] Policy related strategies: formulation of suitable policies and their effective implementation is the key to achieve any purpose. EOL waste management should focus on two main aspects: 1) designingout any waste from future demolition of any project, and 2) maximizing reusing and recycling of various components/elements and materials from the eventual demolition [45] [46]. Policies like financial incentives and subsidies to designers and manufacturers of EOL waste management practices, elements or materials are seen to support such practices [47] [48].…”
Section: Gs04mentioning
confidence: 99%
“…Research and Development (R&D) [15], [30] Policy related strategies: formulation of suitable policies and their effective implementation is the key to achieve any purpose. EOL waste management should focus on two main aspects: 1) designingout any waste from future demolition of any project, and 2) maximizing reusing and recycling of various components/elements and materials from the eventual demolition [45] [46]. Policies like financial incentives and subsidies to designers and manufacturers of EOL waste management practices, elements or materials are seen to support such practices [47] [48].…”
Section: Gs04mentioning
confidence: 99%
“…On the other hand, policymakers and industry practitioners must improve their awareness and efforts to promote and implement effective C&DWM [39]. Albeit, the emergence of building information modeling technology provides new opportunities to reduce construction waste generation and project costs by enhancing the quality of design and construction management with inherent capabilities like material quantity take-off, spatial conflict analysis, and multidisciplinary data communications.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Albeit, the emergence of building information modeling technology provides new opportunities to reduce construction waste generation and project costs by enhancing the quality of design and construction management with inherent capabilities like material quantity take-off, spatial conflict analysis, and multidisciplinary data communications. However, few studies have focused on how to more effectively manage demolition waste generated from existing buildings with the aid of building information modeling applications [39,40]. Han et al [39] identified the main barriers hindering the extensive adoption of building information modeling in C&DWM as the inefficient building data acquisition and integration process, moreover, existing waste management software and inherent waste analytic functionalities are not compatible with building information modeling.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The construction sector is one of the most significant contributors to a nation's growth from social and economic aspects, whereby it raises the living standards of a community [1,2]. It entails the development of socioeconomic projects and infrastructure such as roads, hospitals, schools and universities for the community.…”
Section: Introductionmentioning
confidence: 99%